Plasminogen activator inhibitor-1 reduces cardiac fibrosis and promotes M2 macrophage polarization in inflammatory cardiomyopathy - Baumeier, Christian; Escher, Felicitas; Aleshcheva, Ganna; Pietsch, Heiko; Schultheiss, Heinz-Peter (Basic research in cardiology, 2021)
Plasminogen activator inhibitor-1 (PAI-1) has a cardioprotective function in mice by repressing cardiac fibrosis through TGF-β and plasminogen-mediated pathways. In addition it is known to be involved in the recruitment and polarization of monocytes/macrophages towards a M2 phenotype in cancer. Here, we investigated the expression of PAI-1 in human dilated cardiomyopathy (DCM) and inflammatory dilated cardiomyopathy (DCMi) and its effect on cardiac fibrosis and macrophage polarization. We retrospectively analyzed endomyocardial biopsies (EMBs) of patients with DCM or DCMi for PAI-1 expression by immunohistochemistry. Furthermore, EMBs were evaluated for the content of fibrotic tissue, number of activated myofibroblasts, TGF-β expression, as well as for M1 and M2 macrophages. Patients with high-grade DCMi (DCMi-high, CD3 + lymphocytes > 30 cells/mm 2 ) had significantly increased PAI-1 levels compared to DCM and low-grade DCMi patients (DCMi-low, CD3 + lymphocytes = 14–30 cells/mm 2 ) (15.5 ± 0.4% vs. 1.0 ± 0.1% and 4.0 ± 0.1%, p ≤ 0.001). Elevated PAI-1 expression in DCMi-high subjects was associated with a diminished degree of cardiac fibrosis, decreased levels of TGF-β and reduced number of myofibroblasts. In addition, DCMi-high patients revealed an increased proportion of non-classical M2 macrophages towards classical M1 macrophages, indicating M2 macrophage-favoring properties of PAI-1 in inflammatory cardiomyopathies. Our findings give evidence that elevated expression of cardiac PAI-1 in subjects with high-grade DCMi suppresses fibrosis by inhibiting TGF-β and myofibroblast activation. Moreover, our data indicate that PAI-1 is involved in the polarization of M2 macrophages in the heart. Thus, PAI-1 could serve as a potential prognostic biomarker and as a possible therapeutic target in inflammatory cardiomyopathies.